What do cross-country surveys tell us about social capital? - David Tannenbaum; Alain Cohn; Christian Zünd; Michel André Maréchal (University of Zurich, Department of Economics, 2020)
We validate survey measures of social capital with a new behavioral data set that examines whether citizens report a lost wallet to its owner. Using data from more than 17,000 lost wallets across 40 countries, we find that survey measures of social capital - especially questions concerning generalized trust or generalized morality - are strongly and significantly correlated with country-level differences in wallet reporting rates. A second finding is that lost wallet reporting rates predict unique variation in the outputs of social capital, such as economic development and government effectiveness, not captured by existing measures.
Keywords: C93; C83; Z10; O10; 330; Social capital; trust; honesty; field experiment; surveys